Soybean and bees. - GAZZONI, D. L. (2016)
Soybean cycle. Types of reproductive structure of plants. Soybean growth types. Bees and plants relations. Soybean yield, bees and entomophilus pollination. Pollinators foraging on soybeans. Soybean and pollinators relations. Soybean pest control and the impact on pollinators.